Analysis of the Level of Career Awareness of Junior High School Students in Yogyakarta City - Caraka Putra Bhakti; Difa Ardiyanti; Agus Ria Kumara; Muhammad Alfarizqi Nizamuddin Ghiffari; Tazkiya Auliya Azfin (Universitas Negeri Semarang, 2024)
This research aims to determine the level of career awareness of junior high school students in Yogyakarta. The development of the times will give rise to various new types of work. The importance of having a promising career is understanding and being aware of existing career changes. Career awareness must be developed, especially in junior high school (SMP). Students at the junior high school level are in the initial phase of determining future career steps. When they enter the next career level, it will be directional and easy for students to undertake. The analysis of the level of career awareness in this research can be the basis for developing teaching materials for guidance and counseling services in increasing career awareness for junior high school students, especially in Yogyakarta. Tujuan dari penelitian ini adalah untuk mengetahui tingkat kesadaran karir siswa sekolah menengah pertama di kota Yogyakarta. Perkembangan zaman akan memunculkan berbagai macam jenis pekerjaan baru. Pentingnya memiliki karir yang baik dengan memahami dan menyadari perubahan karir yang ada. Kesadaran karir perlu untuk dikembangkan sejak berada di bangku sekolah khususnya di sekolah menengah pertama (SMP). Siswa pada tingkat SMP menjadi fase awal untuk menentukan Langkah karir kedepan agar ketika memasuki jenjang karir berikutnya akan terarahkan dan mudah untuk dijalani oleh siswa. Analisis tingkat kesadaran karir pada penelitian ini diharapkan menjadi landasan untuk mengembangkan materi bahan ajar layanan bimbingan dan konseling dalam meningkatkan kesadaran karir siswa SMP khususnya di kota Yogyakarta.